تأثير بعض عزلات الفطر Fusarium oxysporum f. sp. Lycopersici في نمو وإصابة هجين البندورة أرجوان - المغربي, صباح; حماد, ياسر; رزق, بشرى (Latakia University Journal -Biological Sciences Series, 2017)
هدفت الدراسة إلى الحصول على عزلات من الفطر Fusarium oxysporum f. sp. lycopersici من نباتات بندورة مزروعة في البيوت المحمية وتبدي أعراض إصابة مميزة لمرض الذبول الوعائي، ودراسة تأثيرها في نمو وإصابة نبات البندورة. تم الحصول على 15 عزلة من الفطر المسبب، واختير منها 8 عزلات ((FO1,FO2,FO3,FO4,FO5,FO6,FO7,FO8 استخدمت في العدوى الاصطناعية لهجين البندورة أرجوان، واختبر تأثيرها في شدة الإصابة، طول المنطقة المصابة، الطول العام للنبات، عدد الأوراق، الوزن الرطب والجاف للمجموعين الخضري والجذري. أظهرت نتائج العدوى بالفطر F. oxysporum f. sp. lycopersiciإصابة الهجين أرجوان بمرض الذبول، وتباينت القدرة الإمراضية للعزلات الفطرية بين (16.67-100%)، وكانت العزلة FO7 أكثر العزلات شراسة إذ بلغت شدة الإصابة بها 100%، ثم تلتها العزلة FO8 بشدة إصابة بلغت 88.33%، كما أظهرت هاتان العزلتان أكبر تأثير في انخفاض طول النبات وعدد الأوراق والوزن الرطب والجاف للمجموعين الخضري والجذري. This study was carried out to obtain Fusarium oxysporum f.sp.lycopersici isolates , off tomato plants were planted under greenhouses with symptoms of fusarium disease, in order to evaluate their effect on the tomato growth.Fifteen isolates of F. oxysporum f. sp. Lycopersici were obtained, and out of those eight were chosen (FO1,FO2,FO3,FO4,FO5,FO6,FO7,FO8) and used as artificial infectors of tomato hybrid Ergwan. The effects of these isolates on the severity of injury, length of browning, plant height, number of leaves, and fresh and dry matter of shoot and root were studied.The result showed that the hybrid Ergwan was infected, where the isolates pathogenicity was between 16.67 – 100%. Our results also showed that the isolate FO7 had the most effect with a injury severity of 100%, followed by the isolate FO8 with 88.33%. These two isolates had the largest low effect on the plant height, number of leaves, and fresh and dry matter of shoot and root.